Punishment and freedom a liberal theory of penal justice - Brudner, Alan. (Oxford : Oxford University Press, 2009)
Presenting an original theory on the nature of crimimal law, this text provides an understanding of apparent contradictions and paradoxes within the field.
Description based on print version record.
Includes index.
Keywords: Punishment; Liberty; Liberalism